The Nature of the Human Corpse Transaction in the Direction of Medical Education - et. al., Farzaneh Kardan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Medical education is of particular importance today. Advances in medical education increase the health index. Medical education is based on autopsy. Increasing the number of corpses for autopsy develops medical education. To this end, some people have donated their bodies after death. To this end, some people have donated their bodies after death. Trading human body after death is the solution that forensic medicine has proposed for eliminate the deficiency of the human body that medical universities need it for medical education. The fatwa of the jurists has proved the correctness of this action, however, there is an important question in this regard what is the nature of the human body trading? Differences in the nature of tradings, pillars and rulings is one of the necessity of this article. The purpose of this article is written with using library resources and descriptive-analytical method, is explanation the religious way that trading of the human body in its form is correct. Using Quranic verses, hadiths of the infallibles and sira Aqla, this result is obtained conditional the trading to the death of the owner of the human body and impossibility of delivering the subject of the trading at the time of its execution and the anonymity of time are the reasons for the invalidity of most tradings of the human body are. The transfer of the human body after death is valid only in the form of a will human body because conditional delivery of commodity does not invalidate the will.